2016
DOI: 10.3892/ijo.2016.3715
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells derived from normal gingival tissue inhibit the proliferation of oral cancer cells in vitro and in vivo

Abstract: The interplay between tumor cells and mesenchymal stem cells (MSCs) within tumor microenvironment plays a significant role in tumor development, and thus might be exploited for therapeutic intervention. In this study, we isolated MSCs from normal gingival tissue (GMSCs), and detected the effect of GMSCs on oral cancer cells via direct co-culture and indirect co-culture systems. The cell proliferation assay of direct co-culture showed that GMSCs could inhibit the growth of oral cancer cells. Conditioned medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 30 publications
(34 reference statements)
1
22
0
Order By: Relevance
“…Human MSCs were isolated and identified according to a previous study (26). Briefly, the primary tissues were treated by dispase (2 mg/ml; Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) in sterile PBS and the mesenchyme part was separated and cut into 2 mm 3 , and then cultured in a 60-mm dish in MSC medium (Sciencell Research Laboratories, Inc., San Diego, CA, USA) for 5-7 days at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Human MSCs were isolated and identified according to a previous study (26). Briefly, the primary tissues were treated by dispase (2 mg/ml; Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) in sterile PBS and the mesenchyme part was separated and cut into 2 mm 3 , and then cultured in a 60-mm dish in MSC medium (Sciencell Research Laboratories, Inc., San Diego, CA, USA) for 5-7 days at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The reason of such discrepancies in terms of MSCs influence on cancer is probably due to the fact that MSCs from different sources may exert various effects on cancer cells. Ji et al [62] suggested that MSCs for anticancer therapy should be derived from the same tissue/organ origin as tumor cells and that they would restore altered homeostasis, exerting anticancer effect.…”
Section: Anticancer Therapiesmentioning
confidence: 99%
“…Moreover, up to 30% of patients with TSCC exhibit metastatic lesions in the lymph nodes, even without the clinical signs of metastasis [64], clearly suggesting that another approaches must be undertaken to enhance the efficiency of cancer treatment. Ji et al [62] cocultured GMSCs with two oral cancer cell lines-CAL27 and WSU-HN6, revealing that MSCs inhibited oral cancer cell growth in vitro. Moreover, their conditioned medium exerted the same effect, suggesting that soluble factors secreted by GMSCs (including IL-6, IL-8, and GM-CSF) may be responsible for such antiproliferative properties.…”
Section: Anticancer Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has demonstrated that MSCs derived from normal gingival tissue secrete soluble factors which inhibit the development of oral cancer. At the molecular level, overexpression of the pro-apoptotic genes p-JNK, cleaved PARP, cleaved caspase-3 and Bax was observed and down-regulation of anti-apoptotic genes: p-ERK1/2, Bcl-2, CDK4, cyclin D1, PCNA and survivin [105].…”
Section: The Osteogenic Potential Of Stem Cells and Its Correlatiomentioning
confidence: 99%